2021
DOI: 10.1061/(asce)co.1943-7862.0002201
|View full text |Cite
|
Sign up to set email alerts
|

Perceived COVID-19 Safety Risk and Safety Behavior on Construction Sites: Role of Safety Climate and Firm Size

Abstract: This study examined the determinants of COVID-19-related safety behavior (SB) on construction sites in Nigeria. Specifically, the effect of perceived COVID-19 safety risk (PCSR) on SB, the interacting (moderating) effect of firm size (FS) on the relationship between PCSR and SB, and the mechanism through which PCSR leads to SB through the firm's safety climate (SC) were examined for a sample of 312 construction site workers in Nigeria. The partial least squares structural equation modeling technique was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 70 publications
1
19
0
Order By: Relevance
“…However, the nature and direction of its effect have not been examined in previous studies. The COVID-19 has made it almost impracticable for project managers to forecast and schedule the workforce needed to execute a project within the stipulated time, which consequently impacts negatively on productivity (Onubi et al, 2021b). Due to the scale in which social distancing has affected the nature and mode of work (Antonacopoulou and Georgiadou, 2020), its effect on schedule performance has become an area of interest for researchers (Akinsomi, 2020), especially the likely mechanism through which the negative effect of social distancing on schedule performance could be minimized or completely eliminated by job re-organization.…”
Section: Introductionmentioning
confidence: 99%
“…However, the nature and direction of its effect have not been examined in previous studies. The COVID-19 has made it almost impracticable for project managers to forecast and schedule the workforce needed to execute a project within the stipulated time, which consequently impacts negatively on productivity (Onubi et al, 2021b). Due to the scale in which social distancing has affected the nature and mode of work (Antonacopoulou and Georgiadou, 2020), its effect on schedule performance has become an area of interest for researchers (Akinsomi, 2020), especially the likely mechanism through which the negative effect of social distancing on schedule performance could be minimized or completely eliminated by job re-organization.…”
Section: Introductionmentioning
confidence: 99%
“…Omatule Onubi et al (2021) explored the determinants of COVID-19-related safety behavior on construction projects in Pirzadeh and Lingard (2021) explored health and well-being experiences in a sample of remote construction professionals and showed a significant relationship between work-life satisfaction and mental well-being during COVID-19. Al-Mhdawi et al captured the impact of COVID-19 on construction projects in developing countries and concluded that contractual implications, construction financial market, supply chain operations, and safety and risk management were four areas mainly impacted by COVID-19.…”
Section: Economic Impacts Of Pandemicsmentioning
confidence: 99%
“…For a typical big project, safety is managed down the hierarchy, but feedback up the hierarchy is usually limited (Woolley et al, 2020). With many contractors and sub-contractors onsite at almost the same time as is the case with most big projects, lines of responsibility for the extra COVID-19 controls can become unclear (Onubi et al, 2021a;Stiles et al, 2020), thus leading to a greater negative effect on EP relative to what is obtainable in small firms. Consequently, the following hypothesis is developed: The negative relationship between COVID-19 safety protocols and EP will be enhanced with big project size.…”
Section: Project Size As a Moderatormentioning
confidence: 99%
“…, 2020). With many contractors and sub-contractors onsite at almost the same time as is the case with most big projects, lines of responsibility for the extra COVID-19 controls can become unclear (Onubi et al. , 2021a; Stiles et al.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%